The Effect of Burner Variation and Modification Toward Combustion Temperature and Effective Time in Husk Gasification - Fikri, Rizqi Raushan, Ir. Subroto, MT, Wijianto, ST, M.Eng.Sc (2016)
Rice husk is one of the most reliable solutions for alternative energy. Husk can produce methane by using gasification technology. By those facts, this research has been held to find out the effect of burner variation and modification toward combustion temperature and effective time in husk gasification. The first step of this method applied all of burners variation and then using modification burner. Thermocouple tip has been put at the centre-bottom of fire for recording temperature changing in every 30 seconds. Combustion temperature measurements were recorded every 30 seconds. The result of experiment from each burners variation are on burner variation without reflector and cap the highest temperature is 612 C and combustion time 35:38 and when use modification burner the highest temperature is 637 C and combustion time 44:10. Burner variation with reflector the highest temperature is 534 C and combustion time 34:50 and when use modification burner the highest temperature is 584 C and combustion time 38:38. Burner variation with cap the highest temperature is 728 C and combustion time 34:20 and when use modification burner the highest temperature is 659 C and combustion time 41:16.